Testing DSGE models by indirect inference and other methods: Some Monte Carlo experiments - Vo Phuong Mai Le; David Meenagh; Patrick Minford; Michael Wickens (Cardiff University, Cardiff Business School, 2012)
Using Monte Carlo experiments, we examine the performance of Indirect Inference tests of DSGE models, usually versions of the Smets-Wouters New Keynesian model of the US postwar period. We compare these with tests based on direct inference (using the Likelihood Ratio), and on the Del Negro-Schorfheide DSGE-VAR weight. We find that the power of all three tests is substantial so that a false model will tend to be rejected by all three; but that the power of the indirect inference tests are by far the greatest, necessitating re-estimation by indirect inference to ensure that the model is tested in its fullest sense.
Keywords: C12; C32; C52; E1; 330; bootstrap; DSGE; New Keynesian; New Classical; indirect inference; Wald statistic; likelihood ratio; DSGE-VAR weight